2019
DOI: 10.1002/jper.18-0630
|View full text |Cite
|
Sign up to set email alerts
|

A peptide derived from rice inhibits alveolar bone resorption via suppression of inflammatory cytokine production

Abstract: Background Periodontitis is an inflammatory disease that results in alveolar bone resorption due to inflammatory cytokine production induced by bacterial antigens such as lipopolysaccharides (LPS). Here, the preventive effect of the Amyl‐1‐18 peptide derived from rice in an experimental model of periodontitis and the effect on the anti‐inflammatory response were assessed. Methods Alveolar bone resorption, gene transcription of proinflammatory cytokines in the gingiva, and the endotoxin level in the oral cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Another peptide from rice, Amyl-1-18, also significantly prevented alveolar bone destruction in mice with ligature-induced periodontitis via suppression of LPS-induced inflammatory cytokine production. These results suggested that the Amyl-1-18 peptide has anti-inflammatory properties against LPS [218].…”
Section: Effects Of Peptides or Proteinsmentioning
confidence: 77%
See 1 more Smart Citation
“…Another peptide from rice, Amyl-1-18, also significantly prevented alveolar bone destruction in mice with ligature-induced periodontitis via suppression of LPS-induced inflammatory cytokine production. These results suggested that the Amyl-1-18 peptide has anti-inflammatory properties against LPS [218].…”
Section: Effects Of Peptides or Proteinsmentioning
confidence: 77%
“…Food-derived peptides have been reported to have a wide range of activities, including antibacterial effects, blood-pressure-lowering effects, antioxidant activities, and cytoprotective or immunomodulatory effects [215,216]; however, little is known about their effects on inflammation and bone resorption in periodontitis. Several researchers have investigated the effects of bioactive peptides derived from foods on periodontitis [217,218]. Local treatment with rice endosperm protein (REP) 9 and 11 significantly inhibited the activity of inflammatory and osteoclast-related molecules and significantly decreased bone resorption in a ligature-induced periodontitis mouse model [217].…”
Section: Effects Of Peptides or Proteinsmentioning
confidence: 99%
“…In experiments in germ‐free animals, the placement of ligatures did not induce significant gingival inflammation or bone loss, 35 which indicates that bacteria are involved in periodontal tissue destruction in ligature models. In addition, it has been reported that bacterial growth and increasing LPS in periodontal tissues in ligature models correlate with increased proinflammatory cytokine production and bone loss, and blocking LPS signaling inhibits bone loss 36,37 . Previous studies have shown that LPS may be involved in gingival inflammation and bone loss in the ligation model 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that bacterial growth and increasing LPS in periodontal tissues in ligature models correlate with increased proinflammatory cytokine production and bone loss, and blocking LPS signaling inhibits bone loss. 36,37 Previous studies have shown that LPS may be involved in gingival inflammation and bone loss in the ligation model. 38 PDL is one of the tissues that responds to mechanical stimulation caused by orthodontic force.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation in the periodontal tissue and bone loss are the main characteristics of periodontitis (Offenbacher, 1996). Periodontal diseases are mediated by the host inflammatory response against bacteria in the periodontal tissue during the process of bone loss (Aoki‐Nonaka et al., 2019). Complex inflammatory signals and molecules, including MMP, RANKL, IL‐1β, IL‐6, TNF‐α, and PGE2, regulate osteoclastogenesis (Araújo et al., 2013).…”
Section: Introductionmentioning
confidence: 99%